Hubungan kadar hematokrit dengan tingkat keparahan pada preeklamsia berat di RSUP H Adam Malik Medan, RSUD dr. Pirngadi Medan dan RS jejaring FK USU - M. Wahyu Wibowo; R. Haryono Roeshadi; Sarma Lumbanraja; Sanusi Piliang; M. Khuwailid; Deri Edianto (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Introduction : Hypertension in pregnancy is one of the causes of maternal morbidity and mortality is high. It cause of 30-40% of perinatal deaths. This state is related to blood viscosity and hematocrit is an important determinant of the blood viscosity. Careful observation of the several indicators, such as hematocrit levels can prevent from unwanted circumstances. Methods : This research is to design pre test - post interventions to determine the relationship between hematocrit levels in preeclampsia before and after childbirth. Pre and post test data is performed using the t test (t-test) and to find the relationship of hematocrit levels with the degree of preeclampsia with Chi-square test.Results : Of the total 55 cases, most cases of severe preeclampsia occurs in the age group 21-35 years were 43 cases (78.2%) cases, have never given birth were 22 cases (40%), history of antenatal care is often enough (4 - 8x during pregnancy) that is found in 30 cases (54.5%), gestational age at term 30 cases (54.5%), and delivery baby with a normal weight in 29 cases (52.7%). Hematocrit levels showed a significant reduction in the time before and after 24 hours of delivery of 34.018 + 0.690 percent to 30.140 ± 0.656 percent (p<0.001). There were no significant differences in hematocrit levels based on the severity of severe preeclampsia both before birth and after 24 hours of labor (p>0.05).Discussion : Found a significant difference in hematocrit levels at the time before and after 24 hours of delivery. Hematocrit levels not influenced by the severity of severe preeclampsia.Keywords : Severe preeclampsia; hematocrit levels